Penggunaan Metode Socrates Dalam Mengembangkan Pendidikan Tinggi Hukum Di Indonesia - Andriati, Syarifah Lisa; Rizki, Inneke Kiki; Binti Mohd Malian, Ain Najwa (UI Scholars Hub, 2025)
The ability to think critically and have the ability as a problem solver is needed in higher education Law in Indonesia. One of the methods used is the Socratic Method. Critical thinking is one of the aspects that law students must have to improve their ability as problem solvers. This research was conducted to contribute that the application of the Socratic method is effective to be applied in the learning process of higher education in Indonesia, as well as to provide evaluation and knowledge about the challenges and obstacles that will be faced in the process of applying the Socratic method in the legal higher education environment in Indonesia. The research method used is legal research, namely by collecting data and references from various sources, then it is arranged systematically through normative juridical analysis. This research produces knowledge that the use of the Socratic method was first carried out in law school by Christopher Columbus Langdell at Harvard University in 1870-1895. The use of the socratic method is useful to help students learn how to use critical thinking skills in analyzing a case, this method is needed to increase self-confidence and practice public speaking skills. The challenges and obstacles in using this method are that there are still educators who ask questions without direction, the need for traditional lecture methods to enhance the socratic method and the need for evidence-based research that is useful for strengthening students' arguments when analyzing a case.